12(r+3)=2(r+5)-4r

Simple and best practice solution for 12(r+3)=2(r+5)-4r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(r+3)=2(r+5)-4r equation:



12(r+3)=2(r+5)-4r
We move all terms to the left:
12(r+3)-(2(r+5)-4r)=0
We multiply parentheses
12r-(2(r+5)-4r)+36=0
We calculate terms in parentheses: -(2(r+5)-4r), so:
2(r+5)-4r
We add all the numbers together, and all the variables
-4r+2(r+5)
We multiply parentheses
-4r+2r+10
We add all the numbers together, and all the variables
-2r+10
Back to the equation:
-(-2r+10)
We get rid of parentheses
12r+2r-10+36=0
We add all the numbers together, and all the variables
14r+26=0
We move all terms containing r to the left, all other terms to the right
14r=-26
r=-26/14
r=-1+6/7

See similar equations:

| -50-z=0 | | 7+20m=35+13m | | 3(x-1)-2x=-11 | | -5(-4v+7)-5v=7(v-6)-3 | | X+1/3x=22/3 | | -6x+4(-2x-6)=-164 | | -7(x+1)-18=11+6 | | 0.5x^2+10x+8=0 | | x/90=133/100 | | 13=-1/3c | | 6x+5=50+ | | 4x-7+2x+1=360 | | 4x-9+3x=4+7x-12 | | 2.5x+.5x=19.5+4.5x | | 2x²-42=5x | | 15x^2-10x-15=0 | | x*3-6+2=20 | | 27x-30=6x2 | | 8x-10+62=180 | | 63/18=x/100 | | 1.94g-10=0.67 | | 8x-9-x+6=57 | | 2(4r+6)=2/3(12r+8) | | 6x+x^2-16=0 | | 13x-3+3x+11=360 | | 3x-9=15+3x | | 6(x-4)=x+3x-10 | | 39-x=-17 | | Xx3-6+2=20 | | 7x-(4x+4)=4x-21 | | 2(5-d)=2-5d | | x^2-11x+28=3 |

Equations solver categories